2020
DOI: 10.3390/su12229664
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Financing of Elite Athlete Development: An Empirical Analysis of Winter Sports in Austria

Abstract: This study examines the value of professional winter sports to the Austrian resident population in the context of three major sporting events (the 2017 World Championships in Alpine Skiing, the 2018 Winter Olympics, and the 2019 World Championships in Nordic Skiing). In nationwide population surveys (n = 2289), the contingent valuation method was employed, and the respondents were presented with two scenarios asking for their willingness-to-pay for live broadcasts and long-term athlete development. The aggrega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
(162 reference statements)
3
8
0
Order By: Relevance
“…Put differently, happier people behave more generously which is reflected in their WTP. The positive association is in line with some existing studies [58], but not all [62]. The insignificant effect in the second model supports the notion that happier people are less generous (e.g., [78]).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Put differently, happier people behave more generously which is reflected in their WTP. The positive association is in line with some existing studies [58], but not all [62]. The insignificant effect in the second model supports the notion that happier people are less generous (e.g., [78]).…”
Section: Discussionsupporting
confidence: 90%
“…Several studies confirmed a positive relationship between well-being and pro-environmental behavior (e.g., [60,61]). Within sport, well-being was positively associated with individuals' WTP [58], but not in all studies (e.g., [62]). The fourth hypothesis reflects these aspects: Hypothesis 4 (H4).…”
Section: Hypothesis 3 (H3)mentioning
confidence: 67%
See 1 more Smart Citation
“…While most studies on residents' perceptions of the economic impacts of mega sports events have focused on individual cities (Coates and Wicker, 2015;Yao and Schwarz, 2018;Wicker and Frick, 2020), this study analyzed the perceptions of residents from all five host cities of AFCON 2022, to delve into the issues that residents are most concerned about. This comprehensive approach implies that the findings and conclusions reveal a nationwide perspective about the respondents' perceptions of the mega event.…”
Section: Discussionmentioning
confidence: 99%
“…This is considered a major omission because the impacts of mega sports events are predominantly at the community level (Li and McCabe, 2013). Wicker and Frick (2020) therefore advise that a community approach be adopted in studies analyzing the impacts of mega sports events. Colomb and Novy (2016) further recommend an inclusive approach that examines multiple perspectives, rather than isolated cases, in the study of community impacts.…”
Section: Introductionmentioning
confidence: 99%